Creativity on the move: Nexus of technology, slack and social complexities - Laurent Antonczak; Thierry Burger-Helmchen (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
While creativity is most commonly associated with idea generation and problem solving at the individual or team level, it is likewise associated with environments, technologies, tools and artefacts favouring or hindering creative capabilities. Research struggles to bring these elements together. We develop a model for the integration of mobile devices into creative processes. More specifically, we elaborate on existing works on creativity to define how firms can make good use of mobile technology in order to enhance the creativity of their employees. Therefore, we suggest a model revisiting the notion of "creative slack" (with the introduction of the notion of mobile slack, or m-slack) and absorptive capacities, explaining how firms might better integrate digital natives; subsequently, we discuss the managerial and theoretical implications.
Keywords: 650; creativity; mobile device; affordance; mobility; slack